Corruption, Business Environment, and Small Business Fixed Investment in India - Honorati, Maddalena; Mengistae, Taye (World Bank, Washington, DC, 2012)
This paper estimates a structural dynamic business investment equation and an error correction model of fixed assets growth on a sample of predominantly small and mid-size manufacturers in India. The results suggest that excessive labor regulation, power shortages, and problems of access to finance are all significant factors in industrial growth in the country. The estimated effects of labor regulation, power shortages and access to finance on the rate of business investment all vary by states' levels of industrial development and. Perhaps more importantly, they also depend on a fourth institutional factor, namely, corruption. The rate of fixed investment is significantly lower where power shortages are more severe and labor regulation is stronger over the full sample, but each of these impacts is also greater for businesses self-reportedly affected by corruption. Although access to finance does not seem to influence the rate of investment for most firms, there is evidence that investment decisions are constrained by cash flow in enterprises that are unaffected by corruption or power shortages. There are nuances to this story as we take into account regional specificity, but the key result always holds that labor regulation, power shortages and access to finance influence the rate of fixed investment in ways that depend on the incidence of corruption. In interpreting this finding, we would like to think of corruption as a proxy for the quality of property rights institutions in the sense of Acemoglu and Johnson (2005). On the other hand, we regard labor regulation and the financial environment of small businesses in India as instances of what Acemoglu and Johnson (2005) call 'contracting institutions'. The analysis finds that the interaction between corruption and other aspects of the institutional environment of fixed investment decisions could be seen consistent with the Acemoglu-Johnson view that the quality of property rights institutions exerts more abiding influence on economic outcomes than the quality of contracting institutions.